2021
DOI: 10.21632/tlj.1.1.1-29
|View full text |Cite
|
Sign up to set email alerts
|

Indonesia’s New Sovereign Wealth Fund: When Strategic Development Converges with Stabilization

Abstract: Indonesia’s latest attempt to reintroduce an investment management agency emerged as the government undertook a significant overhaul of its investment strategy in providing a vehicle to accommodate foreign investment. While the agency had been categorically set as a hybrid model of a stabilization fund as well as a strategic development fund, the interplay between these two objectives remains to be seen by virtue of implementing the agency’s mandate stated in the Job Creation law and its implementing regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…15 of 2006 on the Audit Board of the Republic of Indonesia was passed to set forth the responsibilities and powers of BPK. Our suggestion echoed a previous study on INA, which suggested that BPK's participation in analysing INA's financial reports is justified given the volume of investment flows involved(Pink, 2020;Halim, 2021). In this case, we assert that if 110 110Yustisia Volume 13 Number 1 (April 2024) Sovereign Wealth Fund Development in...…”
supporting
confidence: 76%
See 1 more Smart Citation
“…15 of 2006 on the Audit Board of the Republic of Indonesia was passed to set forth the responsibilities and powers of BPK. Our suggestion echoed a previous study on INA, which suggested that BPK's participation in analysing INA's financial reports is justified given the volume of investment flows involved(Pink, 2020;Halim, 2021). In this case, we assert that if 110 110Yustisia Volume 13 Number 1 (April 2024) Sovereign Wealth Fund Development in...…”
supporting
confidence: 76%
“…Indonesia's SWF differs from Norway's and Singapore's inward-looking approach, focusing on government co-investment with private investors in Indonesia-based projects (Habir, 2021). The idea of SWF was established in 2007 through the Government Innovation Center but was eventually liquidated in 2015 because of the limited amount of Indonesia's reserves (Febriyanta, 2021).…”
mentioning
confidence: 99%